Modification of the Arash Method using Facet Analysis - Ibrahim, Mustapha Daruwana (Eastern Mediterranean University EMU, 2015)
Data Envelopment Analysis, one of the most popular disciplines in operations research, it is a technique used to estimate the performance of Decision Making Units (DMUs). Technical efficient DMUs and Efficient DMUs are difficult to differentiate without the availability of additional information in the form of weight restrictions or the use of statistical technique and supper efficiency method. The Arash method (2013) distinguishes between Technical efficiency and Efficiency by introducing a small error in input values even if the values are accurate, the efficiency scores of the efficient DMUs does not change, only that of the technical efficient DMUs, it also establishes that, for a DMU to be efficient, technical efficiency is one of the necessary conditions. In this study we expand the Arash Method by using facet analysis to modify the PPS of the Arash method. The proposed modification places an upper bound only on the free variable of VRS Arash method. This modification on the Arash method gives the true efficiency score and rank for the weak efficient DMUs and DMUs which take their efficiency score when compared to the weak part, because, the use of facet analysis on the frontier of the Arash method deduced some essential details about the constructive hyper planes of the production possibility set (PPS), Particularly the weak part of the frontier. Keywords: Data Envelopment Analysis, Arash Method, Efficiency, Technical Efficiency, Facet Analysis, Modified Arash method, rank.

ÖZ: Yöneylem araştırmalarında en bilinen disiplin veri zarflama analizidir. Bu analiz Karar Verme Birimleri’nin (KVB) performansını tahmin etmede kullanılan bir tekniktir. Teknik verimli KVB ve verimli KVB’yi birbirinden ayırmak ek bilgi olmadan zordur. Bu ek bilgiler ağırlık kısıtlamaları formundadır veya istatistik tekniği ve süper verimlilik metodu kullanılarak elde edilir. Arash metodu (2013) teknik verimlilik ve verimliliği birbirinden ayırmada giriş değerindeki küçük bir hatanın, değerler doğru olsa bile verimli KVB’deki verimlilik değerini değiştirmeyeceğini, teknik verimli KVB’yi değiştireceğini sunmuştur. Ayrıca, KVB’nin verimli olması için teknik verimlilik gerekli bir durumdur. Bu çalışmada Arash metod, Arash metodun üretim imkanları setini değiştirmek için yön analizi kullanılarak genişletilmiştir. Öngörülen değişim üst sınırda Arash metodun ölçek değişken dönüşünün serbest değişkeninde yapılmıştır. Arash metoddaki bu değişim KVB’lerin gerçek verimlilik hesabını ve zayıf verimlilik derecelerini göstermektedir. KVB’lerin verimlilik hesabı zayıf verimli taraf ile, sınırın özellikle zayıf parçası, karşılaştırıldığında Arash metodun sınırında yön analizi kullanımı sebebiyle, üretim imkanları setinin yapıcı hiperdüzlemleri hakkında bazı temel ayrıntılar ortaya çıkmıştır. Anahtar Kelimeler: Veri Zarflama Analizi, Arash Metod, Verimlilik, Teknik Verimlilik, Yön Analizi, Değiştirilmiş Arash Metod, Derece.
Master of Science in Industrial Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Industrial Engineering, 2015. Supervisor: Assist. Prof. Dr. Sahand Daneshvar.
Keywords: Industrial Engineering; Data envelopment analysis; Data envelopment analysis-Industrial efficiency-Measurement; Industrial productivity-Measurement; Data Envelopment Analysis; Arash Method; Efficiency; Technical Efficiency; Facet Analysis; Modified Arash method; rank